Teaching Academic Writing Skills: A Narrative Literature Review of Unifying Academic Values through Academic Integrity - Hysaj, Ajrina; Khan, Zeenath Reza; Freeman, Mark (Journal of Academic Writing, 2025)
Academic integrity continues to concern educators worldwide. Furthermore, general guidelines for ensuring academic integrity do not seem to encompass all the angles that are required to be taken into consideration when exploring the factors that contribute to multicultural students’ decision to adhere to the norms and values of academic integrity. This literature review focuses on how academic values can be unified through academic integrity, and specifically explores factors and perspectives of utilising academic integrity to unify academic values when teaching academic writing. The dimensions of academic values explored in this paper are: a) beliefs and attitudes of multicultural undergraduate students and the theory of planned behaviour (TPB), b) the value of academic performance in academic writing classes, c) exploring the development of multicultural students’ authorial voice while maintaining academic integrity, and d) using technology to encourage academic integrity in academic writing classes. Over 56 identified sources were chosen carefully to ensure unbiased approaches to the issues of academic integrity and development of academic writing skills. The authors explored the issues from a variety of perspectives. The gap noticed in the review of literature is the disconnection between academic values and academic integrity. The authors make recommendations for future research.